Diversity of coral-associated pit crabs (Crustacea: Decapoda: Cryptochiridae) from Hong Kong, with description of two new species of Lithoscaptus A. Milne-Edwards, 1862 - Wong, Kingsley J. H.; Tsao, Yao-Feng; Qiu, Jian-Wen; Chan, Benny K. K. (Frontiers in Marine Science, 2023)
Highly specialized cryptochirid crabs are obligate symbionts of scleractinian corals in tropical and subtropical seas. The general body morphology of cryptochirid crabs remains poorly described due to their small size and cryptic lifestyles, thus the current inventory is probably an underestimation. In the present study, we sampled cryptochirid crabs from coral communities in Hong Kong, in local literature only Cryptochirus hongkongensis (now Neotroglocarcinus) with unknown hosts had been recorded since 1936. DNA barcoding analysis of the mitochondrial Cytochrome c oxidase I (COI) marker from our samples revealed at least six operative taxonomic units (OTU), representing five species: Cryptochirus coralliodytes, Lithoscaptus paradoxus, L. doughnut sp. nov., L. scottae sp. nov., and Xynomaia sheni species complex. Morphological description of these species is provided, including description of the two new species. The hosts of the genus Lithoscaptus belong largely to the Merulinidae, while L. doughnut sp. nov. inhabits the Plesiastreidae.